Penerapan SAK EMKM dalam Penyusunan Laporan Keuangan Pada UMKM Batik Lea Collection - Oktavie Fresiliasari; Fransiska Tyas Utami (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are business activities that have an important role in expanding employment opportunities and providing broad economic services for the community. However, the obstacles faced by MSMEs are the lack of ability and understanding due to low education and the assumption that the implementation of financial report recording is difficult. Therefore, this study is very interesting because it aims to test the application of SAK EMKM in the preparation of financial statements, especially regarding the application of SAK EMKM in the preparation of financial statements understood by micro, small, and medium enterprises (MSMEs). This study uses descriptive research with qualitative methods. The data collection used was interviews, observations, and documentation. Based on the findings of the research discussion, it can be concluded that Batik Lea Collection MSMEs have not implemented SAK EMKM in the preparation of their financial statements. This is mainly due to the owner's limited knowledge and understanding of accounting and financial reporting standards. Although the owners know about the existence of SAK EMKM, they lack knowledge about its implementation. Evidence from direct observation and documentation shows that Batik Lea Collection MSMEs only record cash inflows and outflows. Owners create bookkeeping reports that can only be understood by themselves